Circulating levels of cyclooxygenase metabolites in experimental Trypanosoma cruzi infections. Issue 4 (2004) - Cardoni, Rita L.; Antúnez, María Inés
Abstract : TRYPANOSOMA cruzi induces inflammatory reactions in several tissues. The production of prostaglandin F2α, 6-keto-prostaglandin F1α and thromboxane B2, known to regulate the immune response and to participate in inflammatory reactions, was studied in mice experimentally infected with T. cruzi. The generation of nitric oxide (NO), which could be regulated by cyclooxygenase metabolites, was also evaluated. In the acute infection the extension of inflammatory infiltrates in skeletal muscle as well as the circulating levels of cyclooxygenase metabolites and NO were higher in resistant C3H mice than in susceptible BALB/c mice. In addition, the spontaneous release of NO by spleen cells increased earlier in the C3H mouse strain. In the chronic infections, the tissue inflammatory reaction was still prominent in both groups of mice, but a moderate increase of thromboxane B2 concentration and in NO released by spleen cells was observed only in C3H mice. This comparative study shows that these mediators could be mainly related to protective mechanisms in the acute phase, but seem not to be involved in its maintenance in the chronic T. cruzi infections.